PENEMPATAN PADA BANK LAIN/PLACEMENT IN OTHER BANKS DAN PENGARUHNYA PADA LABA BERSIH KEGIATAN USAHA BANK UMUM SYARIAH - Ria Kusumaningrum; Riska Puspa; Ridho Dzatilah; Rizki; Decky Saepul Adha (SAHID BANKING JOURNAL, 2022)
Placements with other banks are Investments with Other Sharia Banks both domestically and abroad in the form of, inter-bank Mudharabah investment certificates, mudharabah deposits, mudharabah savings, wadiah current accounts and wadiah savings intended for optimizing fund management. Placements with other banks are a component of earning assets with the aim of optimizing fund management. Therefore the bank must form an allowance to cover possible losses in the same currency. Based on the description above, what needs to be investigated is whether and how Placements in Other Banks are in terms of Current Accounts/Demand Deposits, Savings/Saving Deposits, Deposits/Time Deposits, Guarantee Deposits/Margin Deposits, Sukuk/Sukuk Settlement Funds Sinking Fund, and Others/Others, have a partial or simultaneous effect on Net Income? Then, what are the proposals for contracts regarding Placement in Other Banks in terms of Demand Deposits/Demand Deposits, Savings/Saving Deposits, Deposits/Time Deposits, Guarantee Deposits/Margin Deposits, Sukuk Settlement Fund/Sukuk Sinking Fund, and Others/Others, can increase a better effect on Net Profit? On the basis of this search, this research was conducted and the results were Placements in Other Banks in terms of Current Accounts/Demand Deposits, Savings/Saving Deposits, Deposits/Time Deposits, Guarantee Deposits/Margin Deposits, Sukuk Settlement Fund/Sukuk Sinking Fund , and Others/Others, have no partial effect on Net Income, but simultaneously have an effect on Net Income.